Factors That Can Affect Student Engagement in Learning - Hana, Firyaal; Nugraha, Sidik Indra; Ahmad, Yousef Bani (Universitas Pahlawan Tuanku Tambusai, 2024)
Factors that can affect student involvement in the classroom have a considerable influence on the student learning process. Because internal and external factors are interconnected, students will successfully complete academic activities if they have the will and effort. In addition, support from their environment can also affect student involvement in the learning process. The purpose of this study is to identify all components that can affect student involvement in the learning process in grade XI students of SMA Pusaka Nusantara 2 Bekasi. This study uses a qualitative approach with data collection through interviews and observation. 3 students were selected by the researchers for further interviews and the data were analyzed using Braun & Clarke's thematic analysis. The results of this study are expected to increase understanding of how important internal and external factors are to help increase student involvement in the learning process.